Laminate and composite laminate
By using a protective laminate of the first base layer and the first release layer composed of a resin containing a crystalline polymer, the problems of brittleness and contamination of the inorganic layer in the prior art are solved, and high gas barrier properties and convenience are achieved.
Patent Information
- Application Number
- CN202380059194.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-22
- Filing Date
- 2023-08-10
- Publication Date
- 2025-03-14
AI Technical Summary
The inorganic layer in the prior art has low flexibility and brittleness in the sealing member, which is prone to damage, resulting in a decrease in gas barrier property, and the inorganic layer is light-transmitted and cannot be used to observe abnormalities in the resin layer. Meanwhile, when a layer containing halogen element is used as a protective film, contamination of the resin layer will occur.
The protective laminate consisting of a first base material layer composed of a specific material and a first release layer in contact with it. The first base material layer is composed of a resin containing a crystalline polymer, has a low water vapor transmittance, and improves heat resistance and mechanical strength through crystallization of the crystalline polymer.
It achieves good gas barrier properties even if the thickness is thin, and provides high convenience during storage and operation, avoiding contamination of the resin layer and brittleness of the inorganic layer.
Smart Images

Figure SMS_7
Abstract
Description
Technical Field
[0001] The present invention relates to a laminate that can be effectively used for protecting a layer that can exhibit a function such as a sealing function, and a composite laminate including the laminate. Background Art
[0002] In optical devices such as light-emitting devices and display devices, a sealing member is sometimes provided as a structural element thereof. For example, an organic electroluminescent light emitter (hereinafter, sometimes appropriately referred to as an "organic EL light emitter") generally has an electrode and a light-emitting layer. The light-emitting layer of the organic EL light emitter contains an organic material, which is generally easily degraded when exposed to water. Therefore, in order to inhibit gases such as water vapor in the external air from entering the light emitter, a sealing member with excellent gas barrier performance is sometimes provided on the organic EL light emitter.
[0003] As such a sealing member, it is known to use a resin layer containing a filler as hygroscopic particles. Furthermore, it is known that after manufacturing such a resin layer to be arranged during the storage period of the device, in order to suppress the decline of its hygroscopic function, a state in which a gas-blocking laminate and a release layer are formed on the surface of the resin layer, and then the gas-blocking laminate is adhered to a composite layer with a substrate layer and an inorganic layer as a protective film (reference patent document 1). In the protective film, the inorganic layer shows a function of suppressing the transfer of moisture in the external air to the resin layer. The substrate layer is a layer supporting the inorganic layer, and the release layer is provided in order to make it easy to peel off the protective film from the resin layer when the resin layer is used. By providing such a protective film, it is possible to reduce degradation and keep the resin layer for a long time, and it is possible to greatly improve the convenience of the resin layer when manufacturing and using it.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent document 1: International Publication No. 2017 / 111138 (corresponding publication: specification of U.S. Patent Application Publication No. 2019 / 006623). Summary of the invention
[0007] Problem that the invention aims to solve
[0008] The inorganic layer in the composite layer described in Patent Document 1 has low flexibility and brittle properties in most cases, so the inorganic layer is easily damaged, thereby reducing gas barrier properties. In addition, the inorganic layer is not light-transmissive in most cases, so when the composite layer is attached to the resin layer, it is impossible to observe the resin layer through the composite layer and check for abnormalities.
[0009] From the perspective of avoiding this disadvantage, as a layer that exhibits the protective function of the protective film, a layer other than the inorganic layer may also be considered. However, in most cases, a layer other than the inorganic layer that can exert gas barrier properties is a layer of a substance containing halogen elements such as chlorine. When such a layer is provided as a protective film in contact with the resin layer, the halogen elements will be transferred to the resin layer, which may cause contamination. This contamination may cause deterioration in a device provided with a resin layer.
[0010] In addition, during the storage of the resin layer, for the convenience of storage, the composite laminate formed by laminating the protective film and the resin layer is preferably a composite laminate that can be made into a roll of a long film, and preferably a composite laminate that can make the thin and long film into a small film roll. In addition, from the perspective of convenience when the resin layer is set in the device, it is also preferred that the thickness of the protective film is thin to a certain extent and has good flexibility.
[0011] Therefore, an object of the present invention is to provide a protective laminate having good gas barrier properties even with a thin thickness and high convenience during storage and handling, useful as a protective film for protecting a hygroscopic resin layer, and a composite laminate having such a protective laminate and being well protected.
[0012] Solutions to Solve Problems
[0013] The present inventors have conducted research to solve the above problems. As a result, the present inventors have found that the above problems can be solved by using a protective laminate including a first substrate layer made of a specific material, thereby completing the present invention. That is, according to the present invention, the following solutions can be provided.
[0014] (1) A protective laminate comprising a first substrate layer and a first release layer provided in contact with one or both surfaces of the first substrate layer,
[0015] The first substrate layer is composed of a polymer and has a water vapor transmission rate of less than 1 g / m at 40°C and 90% Rh when the thickness is 100 μm. 2 / day of resin composition.
[0016] (2) The protective laminate according to (1), wherein the polymer is a crystalline alicyclic structure-containing polymer.
[0017] (3) A composite laminate having:
[0018] The protective laminate according to (1) or (2); and
[0019] a resin layer (R) provided in contact with the surface of the protective laminate on the release layer side,
[0020] The weight change rate of the resin layer (R) when left to stand in an environment of 25° C. and 50% Rh for 2 hours is 0.5% or more.
[0021] (4) The composite laminate according to (3), wherein the resin layer (R) contains a hygroscopic filler.
[0022] (5) The composite laminate according to (3) or (4), wherein the composite laminate further comprises a thin film glass, the thin film glass being arranged on the side of the resin layer (R) opposite to the first release layer and having a thickness of 25 to 100 μm.
[0023] (6) The composite laminate according to (3) or (4), wherein the composite laminate further comprises a facing protective laminate, wherein the facing protective laminate is arranged on the side of the resin layer (R) opposite to the first release layer,
[0024] The facing protective laminate comprises a second substrate layer and a second release layer provided in contact with one or both surfaces of the second substrate layer.
[0025] The surface of the facing protective laminate on the second release layer side is arranged in contact with the resin layer (R),
[0026] The second substrate layer comprises a polymer and has a water vapor transmission rate of less than 1 g / m at 40° C. and 90% Rh when the thickness is 100 μm. 2 / day.
[0027] Effects of the Invention
[0028] According to the present invention, there can be provided a protective laminate having good gas barrier properties even though thin, high convenience during storage and handling, useful as a protective film for protecting a hygroscopic resin layer, and a composite laminate having such a protective laminate and being well protected. DETAILED DESCRIPTION
[0029] The present invention will be described in detail below by showing embodiments and examples. However, the present invention is not limited to the embodiments and examples shown below, and can be arbitrarily modified within the scope of the claims of the present invention and their equivalents.
[0030] In the following description, "long strip" refers to a film having a length of 5 times or more relative to the width, preferably 10 times or more, and specifically refers to a film having a length that can be rolled up for storage or transportation. The upper limit of the length is not particularly limited, and is usually 100,000 times or less relative to the width.
[0031] In the following description, unless otherwise specified, expressions such as “(meth)acryl” are terms covering “acryl”, “methacryl” and combinations thereof, for example, “(meth)acrylic acid” is a term covering “acrylic acid”, “methacrylic acid” and mixtures thereof, and “(meth)acrylate” is a term covering “acrylate”, “methacrylate” and mixtures thereof.
[0032] In the following description, unless otherwise specified, the symbol "Rh" in the unit of humidity "%Rh" indicates that the humidity is relative humidity.
[0033] (Overview of the Invention)
[0034] The protective laminate of the present invention is a film having multiple layers that can be used as a protective film. Here, the protective film refers to a film that suppresses moisture absorption of the layer to be protected. Here, moisture absorption of the layer refers to the absorption of components in the external air such as water vapor into the layer. Specifically, suppressing moisture absorption means suppressing the moisture absorption of the hygroscopic layer from absorbing moisture in the external air before use using its hygroscopic ability, and suppressing the hygroscopic ability of the hygroscopic layer from decreasing after the start of use.
[0035] The composite laminate of the present invention is a laminate comprising the protective laminate of the present invention and a resin layer (R) which is a specific resin layer to be protected.
[0036] (Protective laminate)
[0037] The protective laminate of the present invention comprises a first substrate layer and a first release layer disposed in contact with one or both surfaces of the first substrate layer. Here, two layers "disposed in contact" means that they are disposed without another layer between them.
[0038] The term "first" in the first substrate layer and the first release layer is used to distinguish them from the second substrate layer and the second release layer described later. When the difference between them is obvious in the context or when they are collectively referred to, they are sometimes simply referred to as "substrate layer" or "release layer".
[0039] (Resin constituting the first base material layer)
[0040] The first substrate layer is a layer composed of a resin containing a polymer. The polymer may be a crystalline polymer. In the following description, the resin containing a crystalline polymer may be referred to as a "crystalline resin".
[0041] A crystalline polymer is a polymer having crystallinity. Here, a "polymer having crystallinity" refers to a polymer having a melting point Tm. In addition, a polymer having a melting point Tm refers to a polymer whose melting point Tm can be observed using a differential scanning calorimeter (DSC). A crystalline resin contains a crystalline polymer to a certain extent, and thus it itself can also show such crystallinity.
[0042] As crystalline polymers, crystalline alicyclic structure-containing polymers and crystalline polystyrene polymers (refer to Japanese Patent Publication No. 2011-118137) and the like can be cited. Crystalline alicyclic structure-containing polymers are particularly preferred. Generally, alicyclic structure-containing polymers are excellent in transparency, low moisture permeability, dimensional stability and lightness, while crystalline alicyclic structure-containing polymers have extremely low moisture permeability, and are particularly excellent as structural elements of the protective laminate of the present invention. Moreover, in most cases, crystalline alicyclic structure-containing polymers have lower incompatibility with the coating liquid for forming a release layer when forming a release layer than non-crystalline alicyclic structure-containing polymers, so a good release layer can be easily formed. Specifically, it is possible to reduce abnormalities such as the generation of cracks in the release layer.
[0043] The alicyclic structure-containing polymer refers to a polymer that can be obtained by a polymerization reaction using a cyclic olefin as a monomer among polymers having an alicyclic structure in the molecule, or a hydrogenated product thereof. However, the polymer is not limited by its production method.
[0044] As the alicyclic structure, for example, a cycloalkane structure and a cycloolefin structure can be cited. Among these, a cycloalkane structure is preferred from the aspect of easily obtaining a substrate layer having excellent characteristics such as thermal stability. The number of carbon atoms contained in an alicyclic structure is preferably 4 or more, more preferably 5 or more, preferably 30 or less, more preferably 20 or less, and particularly preferably 15 or less. By making the number of carbon atoms contained in an alicyclic structure within the above range, the mechanical strength, heat resistance and moldability of the crystalline resin can be highly balanced.
[0045] In the crystalline polymer, the ratio of the structural unit having an alicyclic structure to the total structural units is preferably 30% by weight or more, more preferably 50% by weight or more, and particularly preferably 70% by weight or more. By making the ratio of the structural unit having an alicyclic structure the above-mentioned high ratio, heat resistance can be improved.
[0046] In addition, in the crystalline polymer, the remaining parts other than the structural unit having an alicyclic structure are not particularly limited and can be appropriately selected depending on the intended use.
[0047] Preferred examples of the crystalline polymer include the following polymers (α) to (δ). Among these, polymer (β) is particularly preferred because a substrate layer having excellent heat resistance can be easily obtained.
[0048] Polymer (α): a crystalline polymer among ring-opening polymers of cyclic olefin monomers.
[0049] Polymer (β): A polymer having crystallinity among hydrogenated products of the polymer (α).
[0050] Polymer (γ): a crystalline polymer among addition polymers of cyclic olefin monomers.
[0051] Polymer (δ): A polymer having crystallinity such as a hydrogenated product of the polymer (γ).
[0052] More specifically, as the crystalline polymer, a polymer having crystallinity among the ring-opening polymers of dicyclopentadiene and a polymer having crystallinity among the hydrogenated products of the ring-opening polymers of dicyclopentadiene are more preferred, and a polymer having crystallinity among the hydrogenated products of the ring-opening polymers of dicyclopentadiene is particularly preferred. Here, the ring-opening polymer of dicyclopentadiene refers to a polymer in which the ratio of the structural unit derived from dicyclopentadiene to the total structural units is usually 50% by weight or more, preferably 70% by weight or more, more preferably 90% by weight or more, and further preferably 100% by weight.
[0053] The crystalline polymer containing an alicyclic structure preferably has a syndiotactic structure, and more preferably a high degree of syndiotactic regularity. This can improve the crystallinity of the polymer, so that the tensile modulus can be particularly large. The degree of syndiotacticity of the crystalline polymer can be represented by the proportion of the racemic diad of the crystalline polymer. The specific proportion of the racemic diad is preferably 51% or more, more preferably 60% or more, and particularly preferably 70% or more. The proportion of the racemic diad can be measured by the method described in the Examples column.
[0054] Furthermore, the crystalline polymer may be used alone or in combination of two or more at any ratio.
[0055] The crystalline polymer may not be crystallized before manufacturing the laminate. However, after manufacturing the laminate of the present invention, the crystalline polymer contained in the laminate can generally have a high degree of crystallinity by crystallization. The specific range of crystallinity can be appropriately selected according to the desired performance, preferably 10% or more, more preferably 15% or more, and particularly preferably 30% or more. By making the crystallinity above the lower limit of the above range, the substrate layer can be given low moisture permeability, high heat resistance and moderate affinity with the coating liquid for forming the release layer.
[0056] The crystallinity of a polymer can be measured by X-ray diffraction.
[0057] The weight average molecular weight (Mw) of the crystalline polymer is preferably 1000 or more, more preferably 2000 or more, and preferably 1000000 or less, more preferably 500000 or less. A crystalline polymer having such a weight average molecular weight has an excellent balance between molding processability and heat resistance.
[0058] The molecular weight distribution (Mw / Mn) of the crystalline polymer is preferably 1.0 or more, more preferably 1.5 or more, and preferably 4.0 or less, more preferably 3.5 or less. Here, Mn represents the number average molecular weight. A crystalline polymer having such a molecular weight distribution has excellent molding processability.
[0059] The weight average molecular weight (Mw) and molecular weight distribution (Mw / Mn) of the polymer can be measured as polystyrene-equivalent values by gel permeation chromatography (GPC) using tetrahydrofuran as a developing solvent.
[0060] The melting point Tm of the crystalline polymer is preferably 200° C. or higher, more preferably 230° C. or higher, particularly preferably 250° C. or higher, and preferably 290° C. or lower. By using a crystalline polymer having such a melting point Tm, a base layer having a better balance between moldability and heat resistance can be obtained.
[0061] The glass transition temperature Tg of the crystalline polymer is not particularly limited, but is usually 85°C or higher and usually 170°C or lower.
[0062] Crystalline polymer preferably has positive intrinsic birefringence value.Polymer with positive intrinsic birefringence value refers to polymer whose refractive index in the stretching direction is larger than the refractive index in the direction orthogonal to it.Intrinsic birefringence value can be calculated by dielectric constant distribution.By adopting crystalline polymer with positive intrinsic birefringence value, substrate layer with good characteristics such as large orientation restriction force, high strength, low cost, low heating dimensional change rate can be easily obtained.
[0063] The method for producing the crystalline polymer is arbitrary. For example, a crystalline polymer containing an alicyclic structure can be produced by the method described in International Publication No. 2016 / 067893.
[0064] The proportion of the crystalline polymer in the crystalline resin is preferably 50% by weight or more, more preferably 70% by weight or more, and particularly preferably 90% by weight or more. By making the proportion of the crystalline polymer greater than the lower limit of the above range, the heat resistance of the substrate layer can be improved.
[0065] The crystalline resin may contain any component in addition to the crystalline polymer. Examples of the optional component include antioxidants such as phenolic antioxidants, phosphorus antioxidants, and sulfur antioxidants; light stabilizers such as hindered amine light stabilizers; petroleum waxes, Fischer-Tropsch waxes, and the like. Waxes such as styryl wax, polyalkylene wax, etc.; nucleating agents such as sorbitol compounds, metal salts of organic phosphoric acid, metal salts of organic carboxylic acid, kaolin, and talc; fluorescent whitening agents such as diaminostilbene derivatives, coumarin derivatives, azole derivatives (such as benzoxazole derivatives, benzotriazole derivatives, benzimidazole derivatives, and benzothiazole derivatives), carbazole derivatives, pyridine derivatives, naphthalene dicarboxylic acid derivatives, and imidazolinone derivatives; UV absorbers such as benzophenone UV absorbers, salicylic acid UV absorbers, and benzotriazole UV absorbers; inorganic fillers such as talc, silica, calcium carbonate, and glass fiber; colorants; flame retardants; flame retardant aids; antistatic agents; plasticizers; near infrared absorbers; lubricants; fillers and any polymers other than crystalline polymers such as soft polymers, etc. In addition, any component may be used alone or in combination of two or more in any ratio.
[0066] The resin constituting the first substrate layer, such as a crystalline resin, preferably does not contain halogen elements or contains a small proportion of halogen elements. Specifically, the proportion (weight ratio) of halogen elements relative to the entire resin is preferably 1500ppm or less, more preferably 900ppm or less. The lower limit of the proportion of halogen elements is ideally 0ppm. By making the proportion of halogen elements within the range described above, the possibility of the film of the protected object such as the resin layer (R) being contaminated by halogen elements can be reduced. Therefore, it is particularly useful when the film of the protected object is a film used near a component that is easily degraded by halogen elements, such as an organic EL light emitter.
[0067] (First substrate layer)
[0068] The first substrate layer has a water vapor transmission rate of less than 1 g / m at 40°C and 90% Rh when the thickness is 100 μm. 2 / day of resin composition.
[0069] The water vapor permeability of the film-like measurement object such as the first substrate layer can be measured using a water vapor permeability meter (e.g., Lyssy L80 series). Furthermore, the water vapor permeability at a thickness of 100 μm can be calculated by the following formula based on the measured water vapor permeability and the thickness of the measurement object. In the following description, the water vapor permeability of the measurement object itself is sometimes referred to as WVTR, and the value of the water vapor permeability when WVTR is converted to 100 μm thickness is referred to as WVTR (100 μm).
[0070]
[0071] The WVTR (100 μm) of the first substrate layer is less than 1 g / m 2 / day, preferably 0.9g / m 2 / day or less, more preferably 0.7g / m 2 / day or less, more preferably 0.5g / m 2 / day or less. The lower limit of water vapor transmission rate is ideally 0g / m 2 / day, which can be, for example, 0.05 g / m 2 By making the first base layer have such WVTR (100 μm), the first base layer itself can exhibit good gas barrier properties even if it is thin, and can provide the protective laminate with good performance as a protective film.
[0072] The first substrate layer having a low WVTR (100 μm) in the above range can be easily obtained by using the above crystalline resin as the constituent resin. In particular, the resin containing a non-crystalline alicyclic structure polymer has a WVTR (100 μm) of 1 g / m in many cases. 2 / day or a value greater than that, whereas the WVTR (100 μm) of the resin containing the crystalline alicyclic structure polymer is less than 1 g / m 2 / day resin, therefore, can be particularly usefully used as a material constituting the first base material layer.
[0073] The thickness of the first substrate layer is preferably 10 μm or more, more preferably 15 μm or more, more preferably 25 μm or more, preferably 150 μm or less, more preferably 100 μm or less, and more preferably 75 μm or less. By making the thickness within this range, it is possible to take into account both good gas barrier properties and high convenience of the composite laminate during storage and operation. Moreover, by making the thickness of the first substrate layer within this range, the first substrate layer can exhibit a desired WVTR.
[0074] The WVTR of the first substrate layer can be adjusted to a desired value by adjusting the thickness of the first substrate layer, etc. so as to achieve a desired gas barrier property. The WVTR of the first substrate layer is preferably 3.0 g / m 2 / day or less, more preferably 2.0g / m 2 / day or less, more preferably 1.2g / m 2 The lower limit of the WVTR of the first substrate layer is not particularly limited, but is preferably 0 g / m 2 / day, can be, for example, 0.2g / m 2 / day or above.
[0075] (Method for producing first base material layer)
[0076] The first base layer can be produced, for example, by a production method including a step of molding a crystalline resin containing a crystalline polymer into a film shape.
[0077] As a molding method of the crystalline resin, it can be manufactured by resin molding methods such as injection molding, extrusion molding, compression molding, inflation molding, blow molding, calendaring molding, casting molding, compression molding, etc. Among these, extrusion molding is preferred from the aspect of easy thickness control.
[0078] In addition, the film produced by the above-mentioned molding method can be used directly as the first substrate layer, or the molded pre-stretched film can be subjected to a stretching treatment to form a stretched film and then used as the first substrate layer. Therefore, the method for producing the first substrate layer can also include the step of stretching the film of the crystalline resin.
[0079] There is no particular limitation on the stretching method, and any stretching method can be used. Examples include uniaxial stretching methods such as a method of uniaxially stretching the film in the longitudinal direction (longitudinal uniaxial stretching method) and a method of uniaxially stretching the film in the width direction (transverse uniaxial stretching method); biaxial stretching methods such as a method of stretching the film in the longitudinal direction and in the width direction at the same time, and a method of sequentially stretching the film in one of the longitudinal and width directions and then in the other direction; and a method of stretching the film in an inclined direction that is neither parallel nor perpendicular to the width direction (oblique stretching method).
[0080] As an example of a longitudinal uniaxial stretching method, a stretching method using the peripheral speed difference between rollers can be cited. As an example of a transverse uniaxial stretching method, a stretching method using a widening stretching machine can be cited. As an example of a simultaneous biaxial stretching method, a widening stretching machine having a plurality of clamps arranged in a manner that can move along a guide rail and can fix the film can be cited, and a stretching method in which the film is stretched in the width direction while the film is stretched in the length direction by the expansion angle of the guide rail while the interval between the clamps is opened. As an example of a sequential biaxial stretching method, a stretching method in which the film is stretched in the length direction by using the peripheral speed difference between rollers, and then the two ends of the film are clamped with a clamp and stretched in the width direction by a widening stretching machine can be cited. As an example of an oblique stretching method, a stretching method in which the film is continuously stretched in an oblique direction using a widening stretching machine that can apply a feed force, a tensile force or a traction force at different speeds to the film in the length direction or the width direction can be cited.
[0081] The stretching temperature is preferably Tg-30°C or higher, more preferably Tg-10°C or higher, preferably Tg+60°C or lower, and more preferably Tg+50°C or lower. Here, "Tg" represents the glass transition temperature of a crystalline polymer. By stretching within such a temperature range, the polymer molecules contained in the film can be appropriately oriented.
[0082] The stretching ratio can be appropriately selected according to the desired optical properties, thickness, strength, etc., and is usually greater than 1 times, preferably more than 1.01 times, more preferably more than 1.1 times, usually less than 10 times, preferably less than 5 times. The stretching ratio is the ratio of the length of the stretched object after stretching to the length before stretching. Here, for example, in the case of stretching in multiple different directions like the biaxial stretching method, the stretching ratio is the total stretching ratio represented by the product of the stretching ratios in each stretching direction. By making the stretching ratio below the upper limit of the above range, the possibility of film rupture can be reduced, so the manufacture of the first substrate layer can be easily performed.
[0083] By subjecting the crystalline resin film to the stretching treatment described above, a first base layer having desired characteristics can be obtained. In addition, a thin and wide first base layer can be easily manufactured.
[0084] In addition, the film manufactured by the above-mentioned manufacturing method can also be subjected to a process of crystallizing the crystalline polymer contained in the film to obtain the first substrate layer. Therefore, the manufacturing method of the first substrate layer can include a crystallization step of crystallizing the crystalline polymer. In the following description, the film that is the object of the process of crystallizing the crystalline polymer is appropriately referred to as a "raw film". The raw film can be a film that has been subjected to a stretching process, or a film that has not been subjected to a stretching process.
[0085] In the crystallization step, generally, a predetermined temperature range is set while at least two end sides of a raw material film made of a crystalline resin are held and stretched, thereby performing a crystallization treatment to crystallize the crystalline polymer. According to this step, a first substrate layer including a crystallized crystalline polymer can be easily manufactured, and thus a first substrate layer having the above-mentioned excellent characteristics can be easily obtained.
[0086] The thickness of the raw material film can be arbitrarily set according to the thickness of the first base material layer, and is usually 5 μm or more, preferably 10 μm or more, and usually 1 mm or less, preferably 500 μm or less.
[0087] The state in which the raw material film is stretched means that tension is applied to the raw material film. However, the state in which the raw material film is stretched does not include the state in which the raw material film is substantially stretched. In addition, substantially stretching means that the stretching ratio of the raw material film in any direction is usually 1.1 times or more.
[0088] When holding the raw material film, the raw material film is held by using an appropriate holding device. The holding device may be a holding device that can continuously hold the entire length of the end edge of the raw material film, or a holding device that can intermittently hold the end edge with intervals. For example, the end edge of the raw material film can be intermittently held by holding devices arranged at predetermined intervals.
[0089] In the crystallization process, the raw material film is in a state where at least two end edges of the raw material film are maintained and stretched. Thus, the raw material film can be prevented from being deformed due to heat shrinkage in the region between the maintained end edges. In order to prevent deformation in a large area of the raw material film, it is preferred to maintain the end edges including the two end edges facing each other so that the region between the maintained end edges becomes stretched. For example, in a single rectangular raw material film, by maintaining the two end edges facing each other (for example, the end edges on the long side or the end edges on the short side), the region between the two end edges becomes stretched, and deformation can be prevented in the entire surface of the single raw material film. In addition, in a long strip raw material film, by maintaining the two end edges located at the ends in the width direction (that is, the end edges on the long side), the region between the two end edges becomes stretched, and deformation can be prevented in the entire surface of the long strip raw material film. The raw material film that has been prevented from deformation in this way can suppress the occurrence of deformation such as wrinkles even if stress is generated in the film due to heat shrinkage. When a stretched film subjected to a stretching treatment is used as the raw film, deformation can be more reliably suppressed by maintaining at least two end sides perpendicular to the stretching direction (a direction with a large stretching ratio in the case of biaxial stretching).
[0090] In order to more reliably suppress deformation during the crystallization process, it is preferred to keep more end edges. Therefore, for example, in a single sheet of raw material film, it is preferred to keep all its end edges. If a specific example is given, in a single rectangular raw material film, it is preferred to keep four end edges.
[0091] As a holder capable of holding the edge of the raw material film, a holder that does not contact the raw material film at a portion other than the edge of the raw material film is preferred. By using such a holder, a first base material layer having better smoothness can be obtained.
[0092] In addition, as a holder, a holder that can fix the relative positions of the holders in the crystallization process is preferred. Such a holder does not move relative to each other in the crystallization process, so it is easy to suppress the substantial stretching of the raw material film in the crystallization process.
[0093] As a preferred holder, for example, as a holder for a rectangular raw material film, there can be cited a clamp such as a clamp that is set on a frame at a predetermined interval and can clamp the end edge of the raw material film. In addition, as a holder for holding two end edges located at the ends of the width direction of a long raw material film, there can be cited a clamp that is set on a tentering stretching machine and can clamp the end edge of the raw material film.
[0094] When using a long raw material film, the end edge (i.e., the end edge on the short side) at the end of the length direction of the raw material film can be maintained, or the two sides of the length direction of the region where the raw material film is subjected to the crystallization treatment can be maintained instead of maintaining the above-mentioned end edge. For example, a holding device that can keep the raw material film in a non-heat-shrinked and tensioned state can be set on both sides of the length direction of the region where the raw material film is subjected to the crystallization treatment. As such a holding device, for example, a combination of two rollers, a combination of an extruder and a traction roller, etc. can be cited. By applying a tension such as a transport tension to the raw material film through these combinations, the thermal shrinkage of the raw material film can be suppressed in the region where the crystallization treatment is performed. Therefore, if the above combination is used as a holding device, the raw material film can be transported along the length direction while the raw material film is maintained, so that the first substrate layer can be efficiently manufactured.
[0095] In the crystallization process, the raw material film is usually set to a temperature above the glass transition temperature Tg of the crystalline polymer and below the melting point Tm of the crystalline polymer while keeping at least two end edges of the raw material film in a tensioned state as described above. In the raw material film set to the temperature as described above, crystallization of the crystalline polymer proceeds. Therefore, through this crystallization process, a film as a first substrate layer containing a crystallized crystalline polymer can be obtained. At this time, since the film is in a tensioned state while preventing deformation of the film, crystallization can be performed without damaging the smoothness of the film.
[0096] As described above, the temperature range in the crystallization process can usually be arbitrarily set within a temperature range above the glass transition temperature Tg of the crystalline polymer and below the melting point Tm of the crystalline polymer. It is particularly preferred to set it to a temperature that increases the rate of crystallization. The temperature of the raw material film in the crystallization process is preferably above Tg+30°C, more preferably above Tg+40°C, preferably below Tm-20°C, and more preferably below Tm-40°C. By making the temperature in the crystallization process below the upper limit of the above range, the turbidity of the first substrate layer can be suppressed, so that a first substrate layer suitable for the case where an optically transparent first laminate is required can be obtained.
[0097] When the raw material film is brought to the above temperature, the raw material film is usually heated. As the heating device used at this time, a heating device that can raise the temperature of the atmosphere of the raw material film is preferred because it is not necessary for the heating device to contact the raw material film. When giving specific examples of preferred heating devices, an oven and a heating furnace can be cited.
[0098] In the crystallization step, the processing time for maintaining the raw material film in the above temperature range is preferably 1 second or more, more preferably 5 seconds or more, preferably 30 minutes or less, and more preferably 10 minutes or less. In the crystallization step, by fully crystallizing the crystalline polymer, the bending resistance of the first substrate layer can be improved. In addition, by making the processing time below the upper limit of the above range, the turbidity of the first substrate layer can be suppressed, so that the first substrate layer suitable for the case where an optically transparent first laminate is required can be obtained.
[0099] In the method for manufacturing the first substrate layer, an arbitrary step may be further performed in combination with the above-mentioned crystallization step. Examples of the arbitrary step include: a relaxation step of thermally shrinking the first substrate layer after the crystallization step to remove residual stress; and a surface treatment step of surface treating the obtained first substrate layer.
[0100] The first base layer can be produced by, for example, the method described in International Publication No. 2016 / 067893.
[0101] (First release layer)
[0102] The first release layer may be disposed in contact with one or both sides of the first substrate layer. That is, the protective laminate of the present invention has a layer structure of (first substrate layer) / (first release layer), a layer structure of (first release layer) / (first substrate layer) / (first release layer) with another first release layer added thereto, or a layer structure obtained by further disposing an additional layer outside these layer structures. Therefore, the protective laminate of the present invention can have one or two first release layers relative to one first substrate layer.
[0103] The first release layer is a layer having releasability. Here, the releasability refers to the property of being easy to peel off. Specifically, the first release layer is a layer with high releasability relative to the layer (resin layer (R), etc.) of the protective laminate as the object of protection. More specifically, the first release layer can be made to have a higher releasability relative to the layer of the protective laminate as the object of protection than relative to the first substrate layer. By having this property, the protective laminate can be easily peeled off when using the layer of the object of protection.
[0104] The first release layer can be formed of a material having a releasable property. The material having a releasable property is not particularly limited, and a material containing a known release agent can be appropriately selected. Examples of release agents include polysiloxane-based release agents and non-polysiloxane-based release agents such as olefins. As the polysiloxane-based release agent, a release agent obtained by curing a release agent containing a curable polysiloxane resin is preferred. Here, the release agent may be a type having a curable polysiloxane resin as a main component, or may be a modified polysiloxane type that can be modified by a polymerization reaction such as graft polymerization with an organic resin such as a polyurethane resin, an epoxy resin, or an alkyd resin.
[0105] As the curable silicone resin, any curing reaction type such as an addition type, a condensation type, an ultraviolet curing type, an electron beam curing type, and a solventless type can be used. When giving specific examples of curable polysiloxane resins, there are KS-774, KS-775, KS-778, KS-779H, KS-847, KS-847T, KS-856, X-62-2422, X-62-2461 manufactured by Shin-Etsu Chemical Co., Ltd.; DKQ3-202, DKQ3-203, DKQ3-204, DKQ3-205, DKQ3-210 manufactured by Dow Corning Asia; YSR-3022, TPR-6700, TPR-6720, TPR-6721 manufactured by Toshiba Silicone Co., Ltd.; SD7220, SD7226, SD7229 manufactured by Toray Dow Corning Co., Ltd. In addition, these release agents may be used alone or in combination of two or more in any ratio.
[0106] Furthermore, in order to adjust the releasability of the first release layer, a release control agent may be used in combination with the release agent. In addition, a catalyst is usually used in combination with the release agent.
[0107] The material constituting the first release layer preferably does not contain halogen elements or contains a small proportion of halogen elements. Specifically, the proportion (weight ratio) of halogen elements relative to all materials constituting the first release layer is preferably 1500ppm or less, more preferably 900ppm or less. The lower limit of the proportion of halogen elements is ideally 0ppm. By making the proportion of halogen elements within the above range, the possibility of the film of the protected object such as the resin layer (R) being contaminated by halogen elements can be reduced. Therefore, it is particularly useful when the film of the protected object is a film used near a component that is easily degraded by halogen elements such as an organic EL light emitter.
[0108] The first release layer can be formed by, for example, applying a release layer forming coating liquid to the surface to be given release properties and curing the coating liquid. The coating liquid can be made into a composition containing a solvent in addition to the above-mentioned components. As the solvent, an organic solvent such as toluene can be appropriately selected and used.
[0109] From the viewpoint of exerting desired performance, the thickness of the release layer is preferably 0.01 μm or more, more preferably 0.03 μm or more, further preferably 0.05 μm or more, and is preferably 1 μm or less, more preferably 0.5 μm or less, further preferably 0.3 μm or less.
[0110] When the first release layer is provided on both the front surface and the back surface of the protective laminate, the thickness of each first release layer is preferably within the above-mentioned preferred range.
[0111] (Structure and properties of protective laminate)
[0112] In the protective laminate of the present invention, the first substrate layer is preferably a layer composed of a resin containing a crystalline alicyclic structure polymer, and more preferably a single layer composed of a resin containing a crystalline alicyclic structure polymer. Furthermore, the protective laminate is preferably a layer having such a first substrate layer and a first release layer, and more preferably a layer consisting only of such a first substrate layer and a first release layer. According to this structure, a protective laminate having high flexibility, suppressing the decrease in gas barrier properties caused by damage, and suppressing the possibility of contamination of the resin layer can be obtained compared to a protective film in the prior art that exerts gas barrier properties through a layer containing an inorganic layer or a halogen element.
[0113] From the viewpoint of reducing the pollution caused by halogen elements, the protective laminate preferably does not contain halogen elements as a whole or contains a small proportion of halogen elements. Specifically, the proportion (weight ratio) of halogen elements relative to the protective laminate as a whole is preferably 1500ppm or less, more preferably 900ppm or less. The lower limit of the proportion of halogen elements is ideally 0ppm.
[0114] The protective laminate preferably has such high transparency that an abnormality of the layer on the opposite side of the observer can be visually inspected through the protective laminate. Specifically, the total light transmittance of the protective laminate is preferably 80% or more, more preferably 85% or more, and particularly preferably 88% or more. The total light transmittance can be measured using an ultraviolet-visible spectrophotometer within a wavelength range of 400nm to 700nm.
[0115] (Composite laminate)
[0116] The composite laminate of the present invention comprises the protective laminate of the present invention and a resin layer (R) disposed in contact with the surface of the release layer side of the protective laminate. That is, the composite laminate of the present invention has a layer structure of (first substrate layer) / (first release layer) / (resin layer (R)) or a layer structure in which an additional layer is further added to the outside of such a layer structure.
[0117] (Resin layer (R))
[0118] When the resin layer (R) is left to stand for two hours in an environment of 25°C and 50% RH, its weight change rate is greater than 0.5%. In order to distinguish it from the weight change rate under other measurement conditions in the following description, the weight change rate under this condition is sometimes referred to as "weight change rate (1)". The weight change rate (1) is not the weight change rate of the resin layer (R) in a state protected by a protective laminate in a composite laminate, but the weight change rate of the resin layer (R) in an unprotected state (for example, a state peeled off from a protective laminate).
[0119] The weight change rate (1) is preferably 1% or more, more preferably 2.5% or more, and further preferably 5% or more. By having such a property, the resin layer (R) can be usefully used in devices such as light-emitting devices and display devices to protect components that will deteriorate due to moisture in the external air, and has a hygroscopic sealing component. Such a resin layer (R) is easy to absorb moisture in the external air during the storage period from manufacturing to assembly in the device, and its performance will deteriorate. By constituting the composite laminate of the present invention, its surface is protected by the protective laminate, and long-term storage with little degradation can be achieved, which can greatly improve the convenience of manufacturing and use of the resin layer (R). The upper limit of the weight change rate (1) is not particularly limited, and can be, for example, 10% or less.
[0120] The weight change rate (1) can be measured by continuously measuring the weight of a sample in a nitrogen atmosphere and a temperature and humidity controlled environment using a moisture adsorption / desorption measuring device (e.g., "IGA sorp" manufactured by HIDEN ISOCHEMA). The measurement can be performed by peeling off the layers other than the resin layer (R) from the composite laminate and using a film consisting only of the resin layer (R) as a sample.
[0121] The control of temperature and humidity can be performed as follows. First, the sample is fully dried and stabilized by treatments of (1-i): 130°C, 0%Rh, 2 hours and (1-ii): 25°C, 0%Rh, 2 hours immediately after (1-i). Immediately thereafter, the sample is placed in an environment of (1-iii): 25°C, 50%Rh, 2 hours. The weight of the sample at the end of (1-ii) is recorded as weight A, and the weight of the sample at the end of (1-iii) is recorded as weight B. Based on these, the weight change rate (1) can be calculated by the following formula.
[0122]
[0123] The resin layer (R) is preferably a layer of a resin containing a hygroscopic filler. Specifically, the resin constituting the resin layer (R) can be a resin containing a polymer and hygroscopic particles as a filler.
[0124] Examples of the polymer include: ethylene-α-olefin copolymers such as ethylene-propylene copolymers; ethylene-α-olefin-polyene copolymers; copolymers of ethylene and unsaturated carboxylic acid esters such as ethylene-methyl methacrylate and ethylene-butyl acrylate; copolymers of ethylene and fatty acid vinyl esters such as ethylene-vinyl acetate; polymers of alkyl acrylates such as ethyl acrylate, butyl acrylate, hexyl acrylate, 2-ethylhexyl acrylate, and lauryl acrylate; diene copolymers such as polybutadiene, polyisoprene, acrylonitrile-butadiene copolymers, butadiene-isoprene copolymers, butadiene-alkyl (meth)acrylate copolymers, butadiene-alkyl (meth)acrylate-acrylonitrile copolymers, butadiene-alkyl (meth)acrylate-acrylonitrile copolymers, butadiene-alkyl (meth)acrylate-acrylonitrile-styrene copolymers; butene-isoprene copolymers ; aromatic vinyl compound-conjugated diene copolymers such as styrene-butadiene random copolymers, styrene-isoprene random copolymers, styrene-butadiene block copolymers, styrene-butadiene-styrene block copolymers, styrene-isoprene block copolymers, styrene-isoprene-styrene block copolymers; hydrogenated aromatic vinyl compound-conjugated diene copolymers such as hydrogenated styrene-butadiene random copolymers, hydrogenated styrene-isoprene random copolymers, hydrogenated styrene-butadiene block copolymers, hydrogenated styrene-butadiene-styrene block copolymers, hydrogenated styrene-isoprene block copolymers, hydrogenated styrene-isoprene-styrene block copolymers; and low-crystalline polybutadiene, styrene-grafted ethylene-propylene elastomers, thermoplastic polyester elastomers, and ethylene-based ionomers. The polymers can be used alone or in combination of two or more.
[0125] In order to obtain the desired effects of the present invention, the polymer is preferably a polymer selected from an aromatic vinyl compound-conjugated diene copolymer, a hydrogenated aromatic vinyl compound-conjugated diene copolymer, and a combination thereof.
[0126] As the aromatic vinyl compound-conjugated diene copolymer, an aromatic vinyl compound-conjugated diene block copolymer is preferred. The aromatic vinyl compound-conjugated diene block copolymer is preferably selected from styrene-butadiene block copolymer, styrene-butadiene-styrene block copolymer, styrene-isoprene block copolymer, styrene-isoprene-styrene block copolymer and mixtures thereof.
[0127] The hydrogenated aromatic vinyl compound-conjugated diene copolymer is a hydrogenated product of the aromatic vinyl compound-conjugated diene copolymer. That is, the hydrogenated aromatic vinyl compound-conjugated diene copolymer has a structure obtained by hydrogenating the carbon-carbon unsaturated bonds of the main chain and side chains of the aromatic vinyl compound-conjugated diene copolymer, the carbon-carbon bonds of the aromatic ring, or a part or all of the two. However, the hydrogenated product of the present application is not limited by its manufacturing method.
[0128] As a further example of the polymer in the resin constituting the resin layer (R), a polymer with a polar group can be cited. The resin preferably includes a polymer with a polar group as a polymer. By making the resin include a polymer with a polar group, the adhesion of the resin layer (R) to the device can be improved. As an example of such a polar group, silicon-containing groups such as alkoxysilyl, carboxyl, anhydride groups and carbonyl-containing groups such as epoxy, amino and isocyanate groups can be cited. Among these, from the viewpoint of making the adhesion with inorganic substances, especially with inorganic substances containing Si such as glass and SiOx good, silicon-containing groups are preferably used, and alkoxysilyl is more preferably used. As a specific example of a polymer with an alkoxysilyl group, a silane-modified product selected from hydrogenated styrene-butadiene block copolymer, a silane-modified product of hydrogenated styrene-butadiene-styrene block copolymer, a silane-modified product of hydrogenated styrene-isoprene block copolymer, and a silane-modified product of hydrogenated styrene-isoprene-styrene block copolymer can be cited. One or more polymers.
[0129] As more specific examples of these polymers and methods for producing them, for example, those described in International Publication No. 2019 / 151142 can be cited.
[0130] The weight average molecular weight (Mw) of the polymer constituting the resin is usually more than 20000, preferably more than 30000, more preferably more than 35000, usually less than 200000, preferably less than 100000, more preferably less than 70000. The weight average molecular weight of the polymer can be measured by the value converted by polystyrene using gel permeation chromatography with tetrahydrofuran as solvent. In addition, the molecular weight distribution (Mw / Mn) of the polymer is preferably less than 4, more preferably less than 3, particularly preferably less than 2, preferably more than 1. By controlling the weight average molecular weight Mw and molecular weight distribution Mw / Mn of the polymer in the above-mentioned range, the mechanical strength and heat resistance of the resin layer (R) can be improved.
[0131] As the hygroscopic particles as fillers contained in the resin constituting the resin layer (R), suitable hygroscopic particles can be appropriately selected from various known hygroscopic particles known to exhibit good hygroscopicity. By containing such fillers, the desired hygroscopicity can be easily imparted to the resin layer (R).
[0132] Examples of materials constituting the hygroscopic particles include: compounds containing alkali metals, alkaline earth metals and aluminum (oxides, hydroxides, salts, etc.) that do not contain silicon (for example, barium oxide, magnesium oxide, calcium oxide, strontium oxide, aluminum hydroxide, hydrotalcite, etc.), organic metal compounds described in Japanese Patent Gazette No. 2005-298598, and alkaline hygroscopic agents such as clay containing metal oxides; acidic hygroscopic agents such as inorganic compounds containing silicon (for example, silica gel, nanoporous silica, zeolite), etc.
[0133] As the material of the hygroscopic particles, it is preferred to select one or more substances from zeolite and hydrotalcite. Zeolite has a particularly high hygroscopic capacity. In addition, zeolite releases water by drying, so it can be reused. On the other hand, hydrotalcite has a short dispersion time when using a bead mill or a wet spray distributor, and is useful in terms of easy and good dispersion. As the material of the hygroscopic particles, one may be used alone, or two or more may be used in combination at any ratio.
[0134] The proportion of hygroscopic particles in the resin constituting the resin layer (R) is preferably 5% by weight or more, more preferably 10% by weight or more, preferably 60% by weight or less, more preferably 40% by weight or less, and further preferably 30% by weight or less. By making the proportion of hygroscopic particles above the above lower limit, the water seepage prevention effect of the resin layer (R) can be improved. In addition, by making the proportion of hygroscopic particles below the above upper limit, the transparency, softness and processability of the resin layer (R) can be improved.
[0135] The resin constituting the resin layer (R) may contain any other components in addition to the above components. Examples of any other components include light stabilizers, ultraviolet absorbers, antioxidants, dispersants, plasticizers, lubricants, inorganic fillers, etc., which are used to improve weather resistance and heat resistance. In addition, any other component may be used alone or in combination of two or more in any ratio.
[0136] As the dispersant, a dispersant having a function of improving the dispersibility of the hygroscopic particles can be appropriately selected for use. Examples of dispersants include polymeric dispersants. In addition, when classified from another point of view, examples of dispersants include acidic dispersants, alkaline dispersants, and neutral dispersants. More specifically, examples of dispersants include alkaline polymeric dispersants, acidic polymeric dispersants, and neutral polymeric dispersants.
[0137] Examples of polymer compounds constituting polymer dispersants include anionic polymer compounds, nonionic polymer compounds, cationic polymer compounds and amphoteric polymer compounds. Examples of anionic polymer compounds include styrene-maleic anhydride copolymers, olefin-maleic anhydride copolymers, naphthalenesulfonate formaldehyde condensates, polycarboxylic acids, esters of polycarboxylic acids, polymethyl sulfonates, acrylamide-acrylic acid copolymers, polyacrylic acid salts, carboxymethyl cellulose and sodium alginate. Examples of nonionic polymer compounds include polyvinyl alcohol, polyoxyethylene alkyl ethers, polyalkylene polyamines, polyacrylamide, polyoxyethylene-polyoxyethylene block copolymers and starch. Examples of cationic polymer compounds include polyethyleneimine, (meth)acrylic acid aminoalkyl ester copolymers, polyvinyl imidazoline and chitosan.
[0138] Examples of dispersants include commercially available dispersants such as the “ARON (registered trademark)” and “JURYMER (registered trademark)” series of Toagosei Co., Ltd., the “AQUALIC (registered trademark)” series of Nippon Catalyst Co., Ltd., the “FLOWLEN (registered trademark)” series of Kyoeisha Chemical Co., Ltd., the “DISPARLON (registered trademark)” series of Kusumoto Chemicals Co., Ltd., the “SOKALAN (registered trademark)” series and “EFKA” series of BASF, the “DISPERBYK (registered trademark)” series and “Anti-Terra” series of BYK Chemical Co., Ltd., the “SOLSPERSE (registered trademark)” series of The Lubrizol Corporation, and the “AJISPER” series of Ajinomoto Fine-Techno Co., Ltd.
[0139] More specific examples of the dispersant include those described in International Publication No. 2019 / 151142.
[0140] As the dispersant, one of those listed above may be used alone, or two or more of them may be used in combination at any ratio.
[0141] The amount of the dispersant is preferably 0.1 parts by weight or more, more preferably 7 parts by weight or more, further preferably 10 parts by weight or more, preferably 1000 parts by weight or less, more preferably 70 parts by weight or less, further preferably 50 parts by weight or less, relative to 100 parts by weight of the hygroscopic particles. By making the amount of the dispersant greater than the above lower limit, it is possible to achieve good dispersion of the hygroscopic particles, reduce internal haze, and achieve high transparency. By making the amount of the dispersant less than the above upper limit, it is possible to suppress the decrease in the adhesion between the resin layer (R) and other components caused by the dispersant.
[0142] Preferred examples of the plasticizer include hydrocarbon oligomers; organic acid ester plasticizers such as monobasic organic acid esters and polybasic organic acid esters; phosphate ester plasticizers such as organic phosphate esters and organic phosphites; and combinations thereof.
[0143] Specific examples of hydrocarbon oligomers include polyisobutylene, polybutene, poly-4-methylpentene, poly-1-octene, ethylene·α-olefin copolymers, polyisoprene, alicyclic hydrocarbons, other aliphatic hydrocarbons, aromatic vinyl compound-conjugated diene copolymers, hydrogenated products of the above compounds, and hydrogenated products of indene·styrene copolymers. Among these, polyisobutylene, polybutene, hydrogenated polyisobutylene, and hydrogenated polybutene are preferred.
[0144] The amount of the plasticizer is preferably 1 part by weight or more, more preferably 5 parts by weight or more, and further preferably 10 parts by weight or more relative to 100 parts by weight of the main component resin of the polymer. On the other hand, it is preferably 60 parts by weight or less, and more preferably 50 parts by weight or less. By making the amount of the plasticizer more than the above lower limit, a sufficient plasticizing effect can be obtained, and low-temperature lamination can be easily performed when the resin layer (R) is set in the device. By making the amount of the plasticizer less than the above upper limit, the exudation of the plasticizer in the case of more than the above parts by weight can be suppressed, and the adhesion between the resin layer (R) and the lamination object can be improved.
[0145] The resin layer (R) preferably does not contain halogen elements or contains a small proportion of halogen elements. Specifically, the proportion (weight ratio) of halogen elements relative to the entire resin layer (R) is preferably less than 1500ppm, more preferably less than 900ppm. The lower limit of the proportion of halogen elements is ideally 0ppm. By making the proportion of halogen elements within the above range, the possibility of the resin layer (R) being contaminated by halogen elements can be reduced. Therefore, it is particularly useful when the resin layer (R) is used near a component that is easily degraded by halogen elements, such as an organic EL light emitter.
[0146] The method for forming the resin layer (R) is not particularly limited, and a common method can be used. For example, the resin layer (R) can be formed by preparing a dispersion containing the above-mentioned components and a solvent, applying it to the surface of the release layer side of the protective laminate, drying the dispersion and volatilizing the solvent.
[0147] Examples of the solvent include those that are liquid at room temperature (preferably 25° C.), and more specifically include cyclohexane, hexane, toluene, benzene, N,N-dimethylformamide, tetrahydrofuran, decalin, trimethylbenzene, methylcyclohexane, ethylcyclohexane, cyclooctane, cyclodecane, n-octane, dodecane, tridecane, tetradecane, cyclododecane, and mixtures thereof.
[0148] (Additional layer: film glass)
[0149] In some examples, the composite laminate of the present invention further comprises a thin film glass having a thickness of 25 to 100 μm and disposed on the side of the resin layer (R) opposite to the first release layer. That is, the composite laminate of this type has a layer structure of (first substrate layer) / (first release layer) / (resin layer (R)) / (thin film glass), or a layer structure in which an additional layer is further added to the outside of such a layer structure.
[0150] Glass plates such as film glass usually have sufficient gas barrier properties. In addition, when the resin layer (R) is used as a structural element of an optical device or the like, the resin layer (R) is often used in a state of being bonded to the film glass as another structural element. The composite laminate having such a film glass in the composite laminate of the present invention is in a state where one side surface of the resin layer (R) is protected by the film glass and the other side surface is protected by a protective laminate (i.e., (first substrate layer) / (first release layer)), and therefore is a laminate in which both sides of the resin layer (R) are protected. Therefore, good storage can be achieved from the manufacture of the composite laminate to the storage period set in the device, and the film glass and the resin layer (R) can be easily installed in the device in a combined state.
[0151] (Additional layers: facing protection laminate: double-sided protection composite laminate)
[0152] In some examples, the composite laminate of the present invention also has a facing protective laminate disposed on the side of the resin layer (R) opposite to the first release layer. The facing protective laminate has a second substrate layer and a second release layer disposed in contact with one or both sides of the second substrate layer, and the surface of the second release layer side of the facing protective laminate is disposed in contact with the resin layer (R). In the present application, for the sake of convenience, a composite laminate that has structural elements such as a facing protective laminate or thin-layer glass in addition to a protective laminate is sometimes specifically referred to as a two-sided protected composite laminate. The two-sided protected composite laminate having a facing protective laminate has a layer structure of (first substrate layer) / (first release layer) / (resin layer (R)) / (second release layer) / (second substrate layer), or a layer structure in which an additional layer is added to the outside of such a layer structure.
[0153] The second substrate layer can be made to contain a polymer and have a water vapor transmission rate of less than 1 g / m at 40° C. and 90% Rh when the thickness is 100 μm. 2 / day layer. By using such a second substrate layer in combination with the first substrate layer to form a double-sided protected composite laminate, good storage can be achieved from the time the composite laminate is manufactured to the time it is placed in the device. Moreover, the resin layer (R) can be easily placed not only on the surface of the film glass, but also on the surface of any structural element in the device.
[0154] As specific examples of the second substrate layer and the second release layer, the same specific examples as those mentioned above regarding the first substrate layer and the first release layer can be cited. In the double-sided protection composite laminate, the second substrate layer and the second release layer may be different from the first substrate layer and the first release layer, but from the viewpoint of ease of manufacture and stable gas barrier properties, they are preferably the same. Specifically, it is preferred to prepare a laminate having a substrate layer and a release layer, cut into a plurality of laminates of appropriate sizes, one of which is used as a protective laminate having a first substrate layer and a first substrate layer, and the other is used as a facing protective laminate having a second substrate layer and a second substrate layer, to form a double-sided protection composite laminate.
[0155] The double-sided protected composite laminate and the composite laminate having a protective laminate and a thin film glass will have a good effect of protecting the resin layer (R). This effect can be evaluated by measuring the weight change rate of the resin layer (R) in the double-sided protected composite laminate. Hereinafter, the weight change rate under such conditions is sometimes referred to as "weight change rate (2)". The weight change rate (2) is the weight change rate of the resin layer (R) in the composite laminate in a state where it is protected by the protected laminate, and is therefore different from the weight change rate (1) in this respect.
[0156] The weight change rate (2) can be measured using the same apparatus as used for measuring the weight change rate (1). In this case, three samples, namely, a film consisting only of the resin layer (R), a protected laminated body alone, and a double-sided protected composite laminated body, are used for measurement.
[0157] In the measurement using the film consisting only of the resin layer (R) as a sample, the weight A and the weight B are recorded in the same manner as in the measurement of the weight change rate (1) described above.
[0158] In the measurement using only the protected laminate as a sample, first, the sample is fully dried and stabilized by treatments (2-1-i): 130°C, 0% Rh, 2 hours and (2-1-ii): 25°C, 0% Rh, 2 hours immediately after (2-1-i). Immediately thereafter, the sample is placed in an environment (2-1-iii): 25°C, 50% Rh, 2 hours. The weight of the sample at the end of (2-1-ii) is recorded as weight C, and the weight of the sample at the end of (2-1-iii) is recorded as weight D.
[0159] In the measurement of the double-sided protected composite laminate as a sample, first, the sample is fully dried and stabilized by (2-2-i): 130°C, 0% Rh, 2 hours and (2-2-ii): 25°C, 0% Rh, 2 hours immediately after (2-2-i). Immediately thereafter, the sample is placed in an environment of (2-2-iii): 25°C, 50% Rh, 2 hours. The weight of the sample at the end of (2-2-ii) is recorded as weight E, and the weight of the sample at the end of (2-2-iii) is recorded as weight F.
[0160] Based on these, the weight change rate (2) can be calculated by the following formula.
[0161]
[0162] The double-sided protected composite laminate of the present invention can make the weight change rate (2) a very small value, for example, 0.2% or less.
[0163] Example
[0164] Hereinafter, the present invention will be specifically described by showing the embodiments. However, the present invention is not limited to the embodiments shown below, and can be arbitrarily changed without departing from the scope of the claims of the present invention and the scope equivalent thereto. In the following description, as long as there is no additional description, the "%" and "part" of the expression amount are weight references.
[0165] [Evaluation method]
[0166] [Method for measuring hydrogenation rate of polymer]
[0167] The hydrogenation rate of the polymer was measured at 145 °C using o-dichlorobenzene-d4 as solvent. 1 The measurement was carried out by H-NMR measurement.
[0168] [Method for measuring weight average molecular weight (Mw) and number average molecular weight (Mn) of polymer]
[0169] The weight average molecular weight (Mw) and number average molecular weight (Mn) of the polymer were measured as polystyrene-equivalent values using a gel permeation chromatography (GPC) system ("HLC-8320" manufactured by Tosoh Corporation). During the measurement, an H-type column (manufactured by Tosoh Corporation) was used as a chromatographic column, and tetrahydrofuran was used as a solvent. In addition, the temperature during the measurement was set to 40°C.
[0170] [Method for determining the ratio of racemic dyads in polymers]
[0171] The proportion of racemic dyads in the polymer is determined as follows.
[0172] The polymer was depolymerized by inverse-gated decoupling at 200 °C using o-dichlorobenzene-d4 as solvent. 13 C-NMR measurement. 13 In the results of C-NMR measurement, the peak of 127.5 ppm of o-dichlorobenzene-d4 was used as the reference shift, and the signal of 43.35 ppm from the meso dyad and the signal of 43.43 ppm from the racemic dyad were analyzed. The ratio of the racemic dyad in the polymer was determined from the intensity ratio of these signals.
[0173] [Method for measuring glass transition temperature Tg, melting point Tm and crystallization peak temperature Tpc of resin material]
[0174] The glass transition temperature Tg and melting point Tm of the resin material are measured as follows.
[0175] The resin material as a sample was melted by heating, and the melt was quenched with dry ice. Next, the glass transition temperature Tg, melting point Tm and crystallization peak temperature Tpc of the sample were measured using a differential scanning calorimeter (DSC) at a heating rate of 10°C / min (heating mode).
[0176] [Measurement method of polymer crystallinity]
[0177] The crystallinity (%) of the polymer was measured by X-ray diffraction.
[0178] [Method for measuring film thickness]
[0179] The thickness (μm) of the film was measured using a contact-type online thickness gauge ("RC-101" manufactured by Meisan Co., Ltd.).
[0180] [Measurement method of total light transmittance of film]
[0181] The film was cut into a size of 50 mm×50 mm, and the total light transmittance of the film was measured using a haze meter (“NDH4000” manufactured by Nippon Denshoku Industries, Ltd.).
[0182] [Measurement method of water vapor transmission rate WVTR of film]
[0183] The water vapor transmission rate WVTR (unit: g / m 2 / day).
[0184] When a protective laminate consisting only of a substrate layer and a release layer is used as a measurement sample, since the water vapor permeability of the release layer is very large, the existence of the release layer can be ignored in the measurement of the water vapor permeability, and therefore the water vapor permeability of the protective laminate can be regarded as the same value as the water vapor permeability of the substrate layer alone.
[0185] Furthermore, the water vapor transmission rate WVTR (100 μm) (unit: g / m) at a thickness of 100 μm was calculated from the measured WVTR value and the thickness of the substrate layer (unit: μm) according to the following formula: 2 / day).
[0186]
[0187] [Method for measuring weight change rates (1) and (2)]
[0188] The weight of the sample was continuously measured in a nitrogen atmosphere and a temperature and humidity controlled environment using a moisture adsorption and desorption measuring device ("IGAsorp" manufactured by HIDEN ISOCHEMA, the same shall apply hereinafter). The measurement was performed using a film having only the resin layer (R) as a sample, a protective laminate as a sample, and a double-sided protected composite laminate as a sample. The temperature and humidity were controlled as follows.
[0189] (Measurement of a film consisting only of the resin layer (R) as a sample)
[0190] (1-i): 130°C, 0%Rh, 2 hours
[0191] (1-ii): Immediately after (1-i), 25°C, 0%Rh, 2 hours
[0192] (1-iii): Immediately after (1-ii), 25°C, 50% RH, 2 hours
[0193] The weight of the sample at the end of (1-ii) is recorded as weight A, and the weight of the sample at the end of (1-iii) is recorded as weight B. Based on these, the weight change rate (1) is calculated by the following formula.
[0194]
[0195] (Measurement using only the protected laminate as a sample)
[0196] (2-1-i): 130°C, 0%Rh, 2 hours
[0197] (2-1-ii): Immediately after (2-1-i), 25°C, 0%Rh, 2 hours
[0198] (2-1-iii): Immediately after (2-1-ii), 25°C, 50% RH, 2 hours
[0199] The weight of the sample at the end of (2-1-ii) is recorded as weight C, and the weight of the sample at the end of (2-1-iii) is recorded as weight D.
[0200] (Measurement using double-sided protected composite laminate as sample)
[0201] (2-2-i): 130°C, 0%Rh, 2 hours
[0202] (2-2-ii): Immediately after (2-2-i), 25°C, 0%Rh, 2 hours
[0203] (2-2-iii): Immediately after (2-2-ii), 25°C, 50% RH, 2 hours
[0204] The weight of the sample at the end of (2-2-ii) is recorded as weight E, and the weight of the sample at the end of (2-2-iii) is recorded as weight F. Based on these, the weight change rate (2) is calculated by the following formula.
[0205]
[0206] [Production Example 1. Production of Crystalline Resin A]
[0207] The metal pressure reactor was fully dried and then replaced with nitrogen. 154.5 parts of cyclohexane, 42.8 parts of a cyclohexane solution of dicyclopentadiene (endomorph content 99% or more) with a concentration of 70% (30 parts based on the amount of dicyclopentadiene), and 1.8 parts of 1-hexene were added to the pressure reactor and heated to 53°C.
[0208] To a solution prepared by dissolving 0.014 parts of tetrachlorotungsten phenylimide (tetrahydrofuran) coordination compound in 0.70 parts of toluene, 0.061 parts of 19% ethoxydiethylaluminum / n-hexane solution was added and stirred for 10 minutes to prepare a catalyst solution. The catalyst solution was added to the above-mentioned pressure-resistant reactor to initiate a ring-opening polymerization reaction. Thereafter, the reaction was carried out for 4 hours while maintaining 53°C to obtain a solution of a ring-opening polymer of dicyclopentadiene.
[0209] The number average molecular weight (Mn) and weight average molecular weight (Mw) of the obtained dicyclopentadiene ring-opening polymer were 8830 and 29800, respectively, and the molecular weight distribution (Mw / Mn) determined therefrom was 3.37.
[0210] To 200 parts of the obtained solution of the ring-opening polymer of dicyclopentadiene, 0.037 parts of 1,2-ethylene glycol as a terminator was added, and the mixture was heated to 60°C and stirred for 1 hour to terminate the polymerization reaction. 1 part of a hydrotalcite-like compound ("KYOWAAD (registered trademark) 2000" manufactured by Kyowa Chemical Industry Co., Ltd.) was added, and the mixture was heated to 60°C and stirred for 1 hour. Thereafter, 0.4 parts of a filter aid ("RADIOLITE (registered trademark) #1500" manufactured by Showa Chemical Industry Co., Ltd.) was added, and the adsorbent and the solution were separated by filtration using a polypropylene pleated cartridge filter ("TCP-HX" manufactured by ADVANTEC Toyo Co., Ltd.).
[0211] To 200 parts of the filtered dicyclopentadiene ring-opening polymer solution (polymer amount 30 parts), 100 parts of cyclohexane and 0.0043 parts of chlorohydrocarbonyltris(triphenylphosphine)ruthenium were added, and a hydrogenation reaction was carried out at a hydrogen pressure of 6 MPa and 180° C. for 4 hours. Thus, a reaction solution containing a hydrogenated product of a dicyclopentadiene ring-opening polymer was obtained. The reaction solution became a slurry solution due to the precipitation of the hydrogenated product.
[0212] The hydride and the solution contained in the reaction solution were separated using a centrifugal separator, and dried under reduced pressure at 60° C. for 24 hours to obtain 28.5 parts of a crystalline hydrogenated ring-opening polymer of dicyclopentadiene. The hydrogenated product was confirmed to have a hydrogenation rate of 99% or more, a glass transition temperature Tg of 97° C., a melting point Tm of 266° C., a crystallization peak temperature Tpc of 136° C., and a racemic dyad ratio of 89%.
[0213] Next, 1.1 parts of an antioxidant (tetrakis[methylene-3-(3′,5′-di-tert-butyl-4′-hydroxyphenyl)propionate]methane; “IRGANOX (registered trademark) 1010” manufactured by BASF Japan) are mixed with 100 parts of the hydrogenated product of the obtained ring-opening polymer of dicyclopentadiene, and the mixture is put into a twin-shaft extruder (manufactured by Toshiba Machine Co., Ltd., “TEM-37B”) having four die holes with an inner diameter of 3 mmΦ. Using the above-mentioned twin-shaft extruder, the resin is molded into a strand-shaped molded body by hot melt extrusion molding. The molded body is chopped using a strand cutter to obtain particles of crystalline resin A. The operating conditions of the above-mentioned twin-shaft extruder are as follows.
[0214] ·Drum set temperature: 270℃~280℃
[0215] Die head set temperature: 250℃
[0216] Screw speed: 145rpm
[0217] [Manufacturing Example 2. Manufacture of Resin Pellets for Forming Resin Layer (R)]
[0218] A hydrogenated block copolymer (hydrogenated block copolymer) was prepared by the following procedure using styrene as an aromatic vinyl compound and isoprene as a chain conjugated diene compound. The produced hydrogenated block copolymer had a triblock structure in which polymer blocks [A] were bonded to both ends of polymer block [B].
[0219] 256 parts of dehydrated cyclohexane, 25.0 parts of dehydrated styrene and 0.615 parts of n-dibutyl ether were added to a reactor having a stirring device and the interior thereof was fully substituted with nitrogen, and 1.35 parts of n-butyl lithium (15% cyclohexane solution) were added while stirring at 60° C. to initiate polymerization, and the reaction was further carried out while stirring at 60° C. for 60 minutes. The polymerization conversion rate at this time was 99.5% (the polymerization conversion rate was measured by gas chromatography. The same shall apply hereinafter).
[0220] Next, 50.0 parts of dehydrated isoprene was added, and stirring was continued at the same temperature for 30 minutes. The polymerization conversion rate at this time was 99%.
[0221] Then, 25.0 parts of dehydrated styrene was further added, and the mixture was stirred at the same temperature for 60 minutes. The polymerization conversion rate at this time was close to 100%.
[0222] Next, 0.5 parts of isopropyl alcohol was added to the reaction solution to terminate the reaction, thereby obtaining a solution (i) containing a block copolymer.
[0223] The block copolymer in the obtained solution (i) had a weight average molecular weight (Mw) of 44,900 and a molecular weight distribution (Mw / Mn) of 1.03 (measured in terms of polystyrene by gel permeation chromatography using tetrahydrofuran as a solvent. The same shall apply hereinafter).
[0224] Next, the solution (i) is transferred to a pressure-resistant reactor with a stirring device, and 4.0 parts of a silica-alumina supported nickel catalyst (E22U, nickel loading 60%; manufactured by JGC Chemical Industries) as a hydrogenation catalyst and 350 parts of dehydrated cyclohexane are added to the solution (i) for mixing. The inside of the reactor is replaced with hydrogen, and hydrogen is supplied while stirring the solution, and a hydrogenation reaction is carried out for 6 hours at a temperature of 170 ° C and a pressure of 4.5 MPa, thereby hydrogenating the block copolymer to obtain a solution (iii) of a hydride (ii) containing a block copolymer. The weight average molecular weight (Mw) of the hydride (ii) in the solution (iii) is 45100, and the molecular weight distribution (Mw / Mn) is 1.04.
[0225] After the hydrogenation reaction is completed, the solution (iii) is filtered to remove the hydrogenation catalyst. Then, 1.0 part of a xylene solution in which 0.1 part of 6-[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propoxy]-2,4,8,10-tetra-tert-butyldibenzo[d,f][1.3.2]dioxaphosphophepane ("SUMILIZER (registered trademark) GP" manufactured by Sumitomo Chemical Co., Ltd., hereinafter referred to as "antioxidant A") as a phosphorus-based antioxidant is dissolved is added to the filtered solution (iii) to dissolve the solution to obtain a solution (iv).
[0226] Next, the solution (iv) is filtered with a ZETA PLUS (registered trademark) filter 30H (manufactured by Kunno Co., Ltd., pore size 0.5 μm to 1 μm), and then filtered in sequence with another metal fiber filter (pore size 0.4 μm, manufactured by NICHIDAI Co., Ltd.) to remove tiny solid components. Using a cylindrical concentrator dryer (product name "Contro", manufactured by Hitachi, Ltd.), cyclohexane, xylene and other volatile components as solvents are removed from the filtered solution (iv) at a temperature of 260°C and a pressure of less than 0.001 MPa. Then, the solid component is extruded into strands in a molten state from a die directly connected to the above-mentioned concentrator dryer, cooled, and chopped with a wire cutter to obtain 85 parts of particles (v) containing a hydrogenated block copolymer and an antioxidant A. The hydrogenated block copolymer in the obtained particles (v) had a weight average molecular weight (Mw) of 45,000 and a molecular weight distribution (Mw / Mn) of 1.08. 1 The hydrogenation rate determined by H-NMR was 99.9%.
[0227] A film-shaped test piece was prepared from the pellet (v), and the glass transition temperature Tg was measured to be 130°C.
[0228] 2.0 parts of vinyl trimethoxy silane and 0.2 parts of di-tert-butyl peroxide were added to 100 parts of the particles (v) to obtain a mixture. The mixture was kneaded using a twin-screw extruder at a barrel temperature of 210° C. and a residence time of 80 to 90 seconds. The kneaded mixture was extruded and cut with a strand cutter to obtain particles (vi) of a silane-modified hydrogenated block copolymer as resin particles for forming a resin layer (R). The glass transition temperature Tg of the particles (vi) was measured to be 124° C.
[0229] [Example 1]
[0230] (1-1. Base material layer)
[0231] The particles of the crystalline resin A obtained in Manufacturing Example 1 were supplied to a hot melt extrusion film forming machine having a T die. The film forming machine was used to extrude the crystalline resin A from the T die, and wound on a roller at a speed of 8 m / min to produce a long raw material film (width 1340 mm). The operating conditions of the above-mentioned film forming machine are as follows.
[0232] ·Cylinder temperature setting: 280℃~290℃
[0233] Die temperature: 270℃
[0234] The thickness of the obtained raw material film was 50 μm.
[0235] The obtained raw film is supplied to a tentering stretching machine with a clamp. The two ends of the film in the width direction are clamped with the clamp of the tentering stretching machine, tensioned, and stretched in the width direction of the film at a stretching temperature of 125°C and a stretching ratio of 1.33 times. After that, the film is passed through a 170°C oven for 30 seconds while the width of the clamp is fixed for crystallization. After that, the two ends of the film in the width direction are cut. Thus, a stretched film with a width of 1300 mm and a thickness of 38 μm used as the first substrate layer is obtained. The obtained stretched film is used as a sample to measure the crystallinity, and the result is 42%.
[0236] (1-2. Coating liquid for forming release layer)
[0237] 10 parts of a curable silicone resin ("LTC761" manufactured by Dow Corning Toray Co., Ltd.) and 0.3 parts of a platinum catalyst ("SRX212" manufactured by Dow Corning Toray Co., Ltd.) were mixed and diluted with toluene to a solid content concentration of 2% to prepare a release layer forming coating liquid.
[0238] (1-3. Protective laminate (first substrate layer / first release layer))
[0239] The coating liquid for forming the release layer obtained in (1-2) is applied to one side of the stretched film obtained in (1-1) to form a coating liquid layer. The coating liquid layer is dried and cured by heating in an oven at 120°C for 3 minutes. As a result, a protective laminate 1 consisting of a first substrate layer and a first release layer provided on the surface thereof is obtained, wherein the first substrate layer is composed of a stretched film.
[0240] The weight per unit area of the first release layer of the protective laminate 1 is 0.12 g / m 2 The water vapor transmission rate WVTR of the protective laminate 1 was measured and the result was 0.7 g / m 2 / day. Since the water vapor permeability of the release layer is very high, the existence of the release layer can be ignored in the measurement of water vapor permeability, so the water vapor permeability of the protective laminate 1 can be regarded as the same value as the water vapor permeability of the substrate layer alone. The water vapor permeability WVTR (100 μm) at a thickness of 100 μm obtained by conversion from the thickness of the substrate layer is 0.27 g / m 2 / day. The total light transmittance of the protective laminate 1 was 91%.
[0241] (1-4. Dispersion Liquid for Forming Resin Layer (R))
[0242] 50 parts of the particles (vi) for forming the resin layer (R) obtained in Production Example 2, 20 parts of polybutene (Nippon Oil & Polybutene LV-100, manufactured by Nippon Oil & Polypropylene Co., Ltd.), 30 parts of hydrotalcite particles (primary particle size 100 nm), 3 parts of a dispersant (SOLSEPERSE 21000, manufactured by The Lubrizol Corporation) and 150 parts of ethylcyclohexane were mixed, and the hydrotalcite particles were crushed by a wet spray dispenser to prepare a dispersion for forming the resin layer (R).
[0243] (1-5. Double-sided protected composite laminate (first substrate layer / first release layer / resin layer (R) / second release layer / second substrate layer))
[0244] The dispersion obtained in (1-4) is applied to the surface on the release layer side of the protective laminate 1 obtained in (1-3) to form a coating film. The thickness of the coating film is adjusted in such a way that the thickness becomes 30 after drying. The coating film of the particle dispersion is dried at 110°C for 3 minutes, and then dried at 130°C for 2 hours in a nitrogen atmosphere, and then the surface of the release layer side of another protective laminate 1 as the opposing protective laminate (i.e. (second release layer) / (second substrate layer)) is immediately pressed on the coating film of the particle dispersion. Through this operation, a two-sided protective composite laminate having a layer structure of (first substrate layer) / (first release layer) / (resin layer (R)) / (second release layer) / (second substrate layer) is obtained.
[0245] (1-6. Evaluation)
[0246] The (first substrate layer) / (first release layer) and (second release layer) / (second substrate layer) were peeled off from the double-sided protected composite laminate obtained in (1-5), the laminate obtained in (1-3), and the double-sided protected composite laminate obtained in (1-5), and a film consisting only of the resin layer (R) was prepared as a sample, and the weight change rate (1) of the resin layer (R) and the weight change rate (2) of the resin layer (R) in the double-sided protected composite laminate were measured. The weight change rate (1) was 5%, and the weight change rate (2) was less than 0.1%.
[0247] In addition, the appearance of the double-sided protected composite laminate was observed with the naked eye to evaluate whether foreign matter in the resin layer (R) (microscopic matter mixed from the outside, matter having properties different from other parts of the resin layer and existing in the resin layer due to material modification or other reasons) could be visually confirmed. The result was that foreign matter in the resin layer (R) could be visually confirmed in both the observation through the first substrate layer and the first release layer and the observation through the second substrate layer and the second release layer.
[0248] [Example 2]
[0249] (2-1. Coating liquid for forming release layer)
[0250] 10 parts of a curable silicone resin ("KS847" manufactured by Shin-Etsu Chemical Co., Ltd.) and 0.15 parts of a platinum catalyst ("PL-50T" manufactured by Shin-Etsu Chemical Co., Ltd.) were mixed and diluted with toluene to a solid content concentration of 2% to prepare a release layer forming coating liquid.
[0251] (2-2. Protective laminate and double-sided protected composite laminate)
[0252] A protective laminate and a double-sided protected composite laminate were obtained and evaluated by the same operation as (1-1) and (1-3) to (1-6) of Example 1 except for the following changes.
[0253] When preparing the base material layer of (1-1), the take-up speed when extruding the crystalline resin A from the T-die was changed from 8 m / min to 12 m / min.
[0254] In the production of the protective laminate of (1-3), the release layer forming coating liquid obtained in (2-1) is used instead of the release layer forming coating liquid obtained in (1-2).
[0255] [Example 3]
[0256] (3-1. Base material layer)
[0257] Prepare pellets of amorphous resin B ("ZEONEX790R" manufactured by Zeon Co., Ltd., Japan) containing 99% by weight of amorphous cyclic olefin polymer (glass transition temperature Tg is 163°C). The pellets of crystalline resin A obtained in Preparation Example 1 and the pellets of amorphous resin B are mixed in a manner such that the weight ratio is crystalline resin A: amorphous resin B = 7:3 and put into a twin-screw kneading extruder (the same as the extruder used in Preparation Example 1). After twin-screw kneading in the extruder, it is extruded into strands from the extruder and chopped with a strand cutter to obtain pellets of the mixed resin. The operating conditions of the twin-screw kneading extruder are as follows.
[0258] ·Drum set temperature = 275 ~ 280 ℃
[0259] Die set temperature = 275°C
[0260] Screw speed = 200rpm
[0261] The obtained mixed resin had a glass transition temperature Tg of 104°C, a melting point Tm of 264°C, and a crystallization peak temperature Tpc of 180°C.
[0262] (3-2. Protective laminate and double-sided protected composite laminate)
[0263] A protective laminate and a double-sided protected composite laminate were obtained and evaluated in the same manner as in Example 1 except for the following changes.
[0264] When preparing the base material layer of (1-1), the pellets of the mixed resin obtained in (3-1) were used instead of the pellets of the crystalline resin A obtained in Production Example 1.
[0265] When preparing the base material layer of (1-1), the temperature of the crystallization treatment was changed from 170°C to 180°C.
[0266] [Comparative Example 1]
[0267] A commercially available release PET film ("HY-US20" manufactured by Higashiyama Film Co., Ltd., hereinafter referred to as the same) was prepared. The release PET film was a product obtained by coating a polysiloxane release layer on one surface of a PET film.
[0268] The particle dispersion obtained in (1-4) of Example 1 is applied to the surface of the release layer side of the release PET film to form a coating. The thickness of the coating is adjusted so that the thickness becomes 30 after drying. The coating of the particle dispersion is dried at 110°C for 3 minutes, and then dried at 130°C for 2 hours in a nitrogen atmosphere, and then the surface of another release PET film on the release layer side is immediately laminated on the coating of the particle dispersion. This operation obtains a double-sided protected composite laminate having a layer structure of (PET film) / (release layer) / (resin layer (R)) / (release layer) / (PET film). The obtained double-sided protected composite laminate is evaluated by the same operation as (1-6) of Example 1.
[0269] [Comparative Example 2]
[0270] Aluminum was sputtered on the side of the release layer of a commercially available release PET film without a release layer using a sputtering device to form an aluminum layer with a thickness of 100 nm, thereby obtaining a protective laminate C2 having a layer structure of (aluminum layer) / (PET film) / (release layer).
[0271] The particle dispersion obtained in (1-4) of Example 1 is applied to the surface of the release layer side of the protective laminate C2 to form a coating film. The thickness of the coating film is adjusted so that the thickness becomes 30 μm after drying. The coating film of the particle dispersion is dried at 110°C for 3 minutes, and then dried at 130°C for 2 hours in a nitrogen atmosphere, and then the surface of another protective laminate C2 on the release layer side is immediately laminated on the coating film of the particle dispersion. Through this operation, a two-sided protective composite laminate having a layer structure of (aluminum layer) / (PET film) / (release layer) / (resin layer (R)) / (release layer) / (PET film) / (aluminum layer) is obtained. The obtained two-sided protective composite laminate is evaluated by the same operation as (1-6) of Example 1.
[0272] [Comparative Example 3]
[0273] A double-sided protected composite laminate was obtained and evaluated by the same operation as in Comparative Example 2 except that the sputtering conditions were changed and the thickness of the aluminum layer was changed from 100 nm to 50 nm.
[0274] Table 1 shows the evaluation results of Examples and Comparative Examples.
[0275] [Table 1]
[0276]
[0277] It was observed that foreign matter in the resin layer (R) could be visually confirmed both in observation from one side (observation through the first base layer and the first release layer) and in observation from the other side (observation through the second base layer and the second release layer).
[0278] Not observable: Foreign matter in the resin layer (R) cannot be visually confirmed in both observation from one surface side and observation from the other surface side.
[0279] From the above results, it can be seen that in the examples of the present application, even a double-sided protected composite laminate having a resin layer (R) with a weight change rate (1) of 5% or more can suppress the weight change rate (2) to a sufficiently low value. The double-sided protected composite laminate of the examples has a structure in which each substrate layer is 25 to 50 μm, the substrate layer itself has gas barrier properties, and does not have other gas barrier layers such as inorganic layers. Therefore, it is possible to ensure sufficient flexibility while maintaining good hygroscopicity, and even a long film can be stored in the form of a thinly packaged film roll.
Claims
1. A protective laminate comprising a first substrate layer and a first release layer disposed in contact with one or both surfaces of the first substrate layer, The first substrate layer is composed of a polymer and has a water vapor transmission rate of less than 1 g / m at 40° C. and 90% Rh when the thickness is 100 μm. 2 / day of resin composition.
2. The protective laminate according to claim 1, wherein The polymer is a crystalline polymer containing an alicyclic structure.
3. A composite laminate having: The protective laminate according to claim 1 or 2; and a resin layer (R) provided in contact with the surface of the protective laminate on the first release layer side, The weight change rate of the resin layer (R) when left to stand in an environment of 25° C. and 50% Rh for 2 hours is 0.5% or more.
4. The composite laminate according to claim 3, wherein: The resin layer (R) contains a hygroscopic filler.
5. The composite laminate according to claim 3, wherein: The composite laminate further includes a thin film glass, which is disposed on a side of the resin layer (R) opposite to the first release layer and has a thickness of 25 to 100 μm.
6. The composite laminate according to claim 3, wherein: The composite laminate further comprises a facing protective laminate, wherein the facing protective laminate is arranged on a side of the resin layer (R) opposite to the first release layer. The facing protective laminate comprises a second substrate layer and a second release layer provided in contact with one or both surfaces of the second substrate layer. The surface of the facing protective laminate on the second release layer side is arranged in contact with the resin layer (R), The second substrate layer comprises a polymer and has a water vapor transmission rate of less than 1 g / m at 40° C. and 90% Rh when the thickness is 100 μm. 2 / day.
Citation Information
Patent Citations
Moisture absorbent for organic el element and organic el element
JP2005298598A
Brightness-enhanced film, method for forming the same, and liquid crystal display device
JP2011118137A
Composite laminate and method for storing resin layer
US20190006623A1
Resin film, barrier film, electrically conductive film, and manufacturing method therefor
WO2016067893A1
Composite laminate and method for storing resin layer
WO2017111138A1